Utilization of Barcodes for Process Efficiency Recap Assignment Grades - Joseph Dedy Irawan; Renaldi Primaswara Prasetya (IJISTECH (International Journal of Information System and Technology), 2022)
One of the learning processes is to give assignments to students with the aim of increasing students' understanding of the material that has been given, besides that assignments can also be used as an evaluation tool for whether students have understood the material. The obstacle faced by lecturers is the process of checking and recapitulating the value of the assignment, where the value of this assignment will also affect the final score of students. Many lecturers use excel to record the value of this assignment, but this process still takes time, especially if the number of students is quite large. The purpose of this research is to create an application with the help of barcodes to help lecturers facilitate the process of recording assignments, by using this barcode the process of finding student numbers will be very easy and fast. The working principle of this application is, students, include their number on their respective assignment sheets in the form of a barcode, then after the assignment is checked and given a grade, the lecturer scans the student ID using a barcode scanner, the application will look for the student ID and the lecturer just enters value, with this system the process of recapitulating tasks will be fast and accurate